Obstetric and newborn outcomes of mothers with and without HIV infection in Anaka general hospital in Northern Uganda - Jolly Joe Lapat; Jimmyy Opee; James Okello; Nixson Oyoo; Christopher Wanican; Gloria Becky Labong; Daniel S. Ebbs; Felix Bongomin (PLoS ONE, 2025)
Background Women of reproductive age constitute a significant proportion of the global HIV burden, with millions becoming pregnant while on lifelong antiretroviral therapy (ART). Although ART has dramatically improved maternal and child health outcomes, concerns persist regarding its safety in pregnancy. This study compares obstetric and neonatal outcomes between women with and without HIV infection at Anaka General Hospital, a rural hospital in northern Uganda. Methods A hospital-based retrospective cross-sectional study at Anaka General Hospital in northern Uganda was conducted from July 2020 to June 2023. A total of 914 delivery records were included, sampled using systematic random sampling from the hospital maternity register. Data were extracted from maternity and neonatal records using a structured tool. Associations between HIV status and obstetric or neonatal outcomes were assessed using Chi-square or Fisher’s exact tests for categorical variables and independent sample t-tests for continuous variables. Multivariable logistic regression was used to adjust for potential confounders and a p < 0.05 was considered statistically significant. Results Of the 914 participants included in the study 38 (4.2%) were HIV-positive. The odds of congenital anomalies were significantly higher among infants born to HIV-positive women compared with HIV-negative women (adjusted odds ratio = 9.76, 95% confidence interval: 1.72–55.48, p < 0.01). No significant differences were observed in maternal or neonatal outcomes between the two groups. Conclusion HIV infection was significantly associated with an increased risk of congenital anomalies, while other obstetric and neonatal outcomes were similar between HIV-positive and HIV-negative women. We recommend enhanced prenatal monitoring and early fetal screening among HIV-positive pregnant women on dolutegravir-based ART. Additionally, prospective studies are needed to better understand the contribution of dolutegravir and maternal factors to congenital anomalies in HIV-exposed pregnancies.